A STUDY OF THE URBAN FEATURES OF THE URBAN SYSTEM IN THE ALGERIAN CITY OF CONSTANTINE FOR THE PERIOD (1987–2022) - Nacer Fethi (International Journal of Innovative Technologies in Social Science, 2024)
The study of the urban system today is one of the important topics in the field of regional planning and urban engineering. It focuses on urban centers from both external and internal perspectives, considering their interaction and interconnection in forming the urban system. This study attempts to explore the characteristics of the urban system in the city of Constantine over the period (1987–2022) by addressing the various changes that occurred in the dynamics of urban movement as well as the manifestations of regional integration and their influence on the city’s size and functions. The study also emphasizes the importance of examining the balance within the urban system and its interactions within the urban network. The results of the study indicate that the characteristics of the urban system exhibit urban dynamics that have developed over a specific period, reflecting a distinctive urban system during a phase where the phenomenon of "urban sprawl" has emerged in alignment with the interests of the city of Constantine. Over time, the urban system evolved to lean towards institutional and legislative balances and the stability of urban networks, while dismantling spatial disparities and integrating the connections within the urban network.